2002
DOI: 10.1161/01.cir.0000036596.59665.c6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Numbers of Tissue-Factor Exposing Microparticles Correlate With Components of the Metabolic Syndrome in Uncomplicated Type 2 Diabetes Mellitus

Abstract: Background— Type 2 diabetes is associated with accelerated atherosclerosis. Because cell-derived microparticles support coagulation and inflammation, they may be involved in atherogenesis. We characterized circulating microparticles both in patients with uncomplicated, well-regulated type 2 diabetes and in healthy subjects, as well as their relationship with coagulation and metabolic control. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
249
5
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(268 citation statements)
references
References 38 publications
12
249
5
2
Order By: Relevance
“…For instance, platelet-derived microparticles are positively associated with abnormal carotid and intima-media thickness and body mass index in obese patients [21]. In addition, microparticles from platelets positively correlate with plasma glucose and insulin levels whereas microparticles from T-helper cells positively and negatively correlate with body mass index (BMI) and HDL-cholesterol, respectively [12].…”
Section: Microparticles Are Biomarkers For Cardiovascular Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, platelet-derived microparticles are positively associated with abnormal carotid and intima-media thickness and body mass index in obese patients [21]. In addition, microparticles from platelets positively correlate with plasma glucose and insulin levels whereas microparticles from T-helper cells positively and negatively correlate with body mass index (BMI) and HDL-cholesterol, respectively [12].…”
Section: Microparticles Are Biomarkers For Cardiovascular Pathologiesmentioning
confidence: 99%
“…However, this hypothesis has been little studied. Thus, circulating levels of microvesicles from platelets [11] and tissue-factor-positive microvesicles from T cells or neutrophils [12] negatively correlate with plasma HDL levels. Finally, with regard to microparticle composition, it has been reported that microparticles envelope and protect mRNA and miRNA from extracellular ribonuclease degradation and in this way represent veritable cargo allowing intercellular communication [13].…”
Section: Introductionmentioning
confidence: 99%
“…VLDL can also up-regulate PAI-1 gene expression, thus increasing the PAI-1 concentration and activity in plasma -a process that is strongly associated with increased platelet aggregation and clot formation (120)(121)(122)(123)(124)(125)136). Finally, it has also been shown that the amount of platelet microparticles, small membrane vesicles that support the coagulation by exposure of anionic phospholipids and TF, is closely associated with the increasing number of the components of the metabolic syndrome (137).…”
Section: Platelet Hyperactivitymentioning
confidence: 99%
“…In addition to coagulation and vascular inflammation, numerous studies indicate that MVs are also involved in angiogen- [81] . Tsimerman et al found that incubation of HUVECs with MVs from patients with severe diabetic foot ulcers could induce the formation of stable and branched networks [35] , suggesting the key role of MVs in angiogenesis and the skin wound healing process in diabetes.…”
Section: Mvs and Angiogenic Effectsmentioning
confidence: 99%